2023
DOI: 10.3390/ijerph20020982
|View full text |Cite
|
Sign up to set email alerts
|

Association and Risk Factors for Hypertension and Dyslipidemia in Young Adults from Poland

Abstract: Hypertension and dyslipidemia are major risk factors for cardiovascular disease. Studies on the association between abnormal levels of lipids and hypertension have yielded inconsistent results. The aim of this study was to examine the prevalence of hypertension and dyslipidemia and its risk factors in young Polish adults. Furthermore, the association between plasma lipid levels and the risk of hypertension was determined. A cross-sectional study was conducted among 115 volunteer participants. Blood pressure wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
3

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 34 publications
1
6
0
3
Order By: Relevance
“…Various epidemiological studies have shown the coexistence of dyslipidemia and hypertension in a range of 15 to 31% 30 . Some studies may not find a direct association between the two conditions 30,31 . The relationship between hypertension and dyslipidemia in Iran underscores the importance of addressing these conditions collectively due to their shared risk factors and impact on cardiovascular health.…”
Section: Discussionmentioning
confidence: 99%
“…Various epidemiological studies have shown the coexistence of dyslipidemia and hypertension in a range of 15 to 31% 30 . Some studies may not find a direct association between the two conditions 30,31 . The relationship between hypertension and dyslipidemia in Iran underscores the importance of addressing these conditions collectively due to their shared risk factors and impact on cardiovascular health.…”
Section: Discussionmentioning
confidence: 99%
“…Esto podría deberse a que la costa peruana se caracteriza por tener población mayoritariamente urbana (20) , donde también se presenta un elevado número de hipertensos a comparación del área rural. Esta concentración de hipertensión en las zonas urbanas puede responder a que las personas son menos activas físicamente y son más propensas a fumar y consumir alcohol (21) . El conocer la real distribución espacial de una de las enfermedades no transmisibles más prevalentes como la hipertensión arterial, es útil para reconocer puntos estratégicos que permitan focalizar estrategias preventivas inmediatas.…”
Section: Discussionunclassified
“…Previous studies have identified various sociodemographic factors for hypertension, but none have examined these factors in the context of the COVID-19 pandemic 24 , 25 . A previous study reported that individuals > 60 years, men, and those with lower education and income levels were at a greater risk of hypertension 3 , 26 .…”
Section: Discussionmentioning
confidence: 99%